THE EFFECTIVENESS OF THE BLENDED LEARNING MODEL ON THE STUDENTS’ CRITICAL THINKING SKILLS AND LEARNING MOTIVATION IN ACCOUNTING DEPARTMENT - Della Fadhilatunisa; Rosidah Rosidah; M Miftach Fakhri (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:The accountant profession in the 21st century requires good critical thinking skills so that developing the skills needed in the 21st century is necessary in the accounting student’ learning environment. Therefore, the technology can be used as a medium for learning and communication between the students and the lecturers. In addition, the problem based learning model as a learning that requires the students to actively participate in each learning to develop the critical thinking skills so that the integration between problem-based face-to-face learning and learning utilizing technology in e-learning media is expected to improve the students’ critical thinking skills and the learning motivation. The research aims to: (1) find out the implementation of an effective blended learning model towards the students’ critical thinking skills and the learning motivation, and (2) to find out the difference in the students’ critical thinking skills and the learning motivation between the experimental class and the control class. This research is a quasi experimental research with non equivalent control group design. The study used one experimental group and one control group. The population in this study was the students who took introductory courses in accounting and accounting information systems so that the samples were taken by using purposive sampling technique. The instruments used are the essay test for the critical thinking skills and the questionnaire for the learning motivation. The data analysis techniques used are paired sample t test and independent sample t test assisted by SPSS 26.00. The findings show that: (1) the results of the paired simple t test show that the implementation of the blended learning model effectively improve the students’ critical thinking skills and the learning motivation, and (2) The results of the independent simple t test show that the students’ critical thinking skills and the learning motivation of the experimental class have a significant difference with the students of the control class.Abstrak:Profesi akuntan pada abad 21 membutuhkan keterampilan berpikir kritis yang baik sehingga diperlukan lingkungan belajar mahasiswa akuntansi yang mampu mengembangkan keterampilan yang dibutuhkan di abad 21. Oleh karena itu, teknologi dapat dimanfaatkan sebagai media untuk belajar dan komunikasi antara mahasiswa dan dosen. Selain itu, model problem based learning sebagai pembelajaran yang menuntut mahasiswa berpartisipasi aktif dalam setiap pembelajaran untuk mengembangkan keterampilan berpikir kritisnya sehingga integrasi antara pembelajaran tatap muka berbasis problem based learning dengan pembelajaran yang memanfaatkan teknologi di media e-learning diharapkan dapat meningkatkan keterampilan berpikir kritis dan motivasi belajar mahasiswa. Adapun penelitian ini bertujuan untuk: (1) mengetahui implementasi model blended learning yang efektif terhadap keterampilan berpikir kritis dan motivasi belajar mahasiswa, (2) mengetahui perbedaan keterampilan berpikir kritis dan motivasi belajar mahasiswa antara kelas eksperimen dengan kelas control. Penelitian ini merupakan quasi experimental dengan desain non equivalent control group design. Penelitian ini menggunakan satu kelompok eksperimen dan satu kelompok kontrol. Populasi pada penelitian ini adalah mahasiswa yang mengambil mata kuliah pengantar akuntansi dan sistem informasi akuntansi sehingga sampel diambil secara purposive sampling. Teknik pengumpulan data untuk keterampilan berpikir kritis adalah tes sedangkan untuk motivasi belajar menggunakan angket. Teknik analisis data yang digunakan adalah paired sample t test dan independent sample t test dengan bantuan SPSS 26.00. Hasil penelitian menunjukkan: (1) Hasil uji paired simple t test menunjukkan implementasi dari model blended learning secara efektif meningkatkan keterampilan berpikir kritis dan motivasi belajar mahasiswa, (2) Hasil uji independent simple t test menunjukkan keterampilan berpikir kritis dan motivasi belajar mahasiswa kelas eksperimen memiliki perbedaan secara signifikan dengan mahasiswa kelas kontrol.